Counting and marking time from the precolonial to the contemporary Tagalog world - Woods, Damon L. (Quezon City Ateneo de Manila University, 2011)
"This Spanish intrusion resulted in cultural and linguistic changes in Philippine societies, but did not lead to a complete exchange of the indigenous for the foreign. The changes were not imposed but rather chosen by the local population, as demonstrated by changes in counting and marking time in Tagalog society, which this article traces, beginning with Tomas Pinpin's Librong pagaaralan nangn manga Tagalog nanag uicang Castila (1610), to the present. Using the categories of core values (animism) and surface values (Spanish Catholicism), this article explains the resulting hybridity evident today."
Keywords: Catholics -- Philippine history; Catholicism; Spanish colonialism